Internet email protocols : a developer's guide - Johnson, Kevin (Addison-Wesley, 2000)
"Internet Email Protocols gathers, in one comprehensive and convenient resource, the key technologies that form the underlying mechanics of Internet email. It provides developers and networking professionals with in-depth explanations of essential concepts and a framework for understanding how and why these technologies fit together to provide cohesive email services. This book shows how to troubleshoot and solve email problems, how to evaluate different implementations of the standards and protocols, and how to be better equipped when faced with the challenge of writing programs that process email."--BOOK JACKET.